"Like–like" tetrel bonding interactions between Sn centres: a combined ab initio and CSD study. Issue 30 (26th June 2019) - Franconetti, Antonio; Frontera, Antonio
Abstract : In this manuscript, we combine a search in the Cambridge Structural Database (CSD) and ab initio calculations (RI-MP2/def2-TZVP level of theory) to analyse the ability of Sn to establish 'like–like' tetrel bonding interactions. Abstract : In this manuscript, we combine a search in the Cambridge Structural Database (CSD) and ab initio calculations (RI-MP2/def2-TZVP level of theory) to analyse the ability of Sn to establish 'like–like' tetrel bonding interactions. The CSD inspection revealed that noncovalent Sn⋯Sn contacts are common in X-ray structures and that two predominant structural patterns exist. Moreover, the nature of like–like tetrel bonding interactions was investigated in a total of 81 dimers by wave function and ab initio (MP2)-based methods. In these dimers the σ-hole donor molecules are para -substituted-phenylstannane derivatives (SnH3 Ar, where Ar = p -YC6 H4 ) and the electron rich molecules are para -substituted-2, 6-dimethylstannabenzenyl anions [2, 6-dimethyl-4-X-C5 H4 Sn(−)], where X, Y = Me2 N, H2 N, t Bu, H, F, CF3, CN, P(CN)2 and SO2 CN. The binding energies calculated at the RI-MP2 level of theory yield an energy scale of 2–13 kcal mol −1 which is comparable to that of hydrogen bonds and demonstrates that Sn⋯Sn interactions can be considered relevant for determining supramolecular assemblies in the solid state and constitute an underexplored inorganic structural motif that can be used in crystal engineering. The utilization of different substituents allows us to study their influence upon the interaction energies. We have obtained Hammett's plots for the two combinations (X = H and Y variable or Y = H and X = variable) and in both cases we have obtained good regression plots (interaction energies vs. Hammett's σ parameter). Finally, we have used Bader's theory of "atoms-in-molecules" to show that the electron density computed at the bond critical point that connects both Sn atoms correlates with the strength of this noncovalent interaction.